Artemisinin: A Panacea Eligible for Unrestrictive Use? - Yuan, Dong-Sheng; Chen, Yan-Ping; Tan, Li-Li; Huang, Shui-Qing; Li, Chang-Qing; Wang, Qi; Zeng, Qing-Ping (Frontiers in Pharmacology, 2017)
Although artemisinin has been used as anti-malarial drug, accumulating evidence on the extended therapeutic potential of artemisinin emerges. Apart from anti-malaria and anti-tumor, artemisinin can also exert beneficial effects on some metabolic disorders, such as obesity, diabetes, and aging-related diseases. However, whether artemisinin should be applied to treatment of the wide-spectrom diseases is debating. Here we discuss the predisposition of a raised risk of malarial resistance to artemisinin from consideration of the multi-target and non-specific features of artemisinin.